Qualitative longitudinal analysis of livestock farming in the ibagué fan region (Tolima, Colombia) (2023)
Background. The Fan of Ibagué is one of the most important livestock and agricultural regions in the country, which faces a sustainability crisis and whose origins can be a critical point for understanding it. Objective. To understand the historical processes of settlement of the Ibague fan and the development of the rice and livestock industries in the region. Methodology. This historical perspective is constructed from agroecology, a transdisciplinary science that seeks to understand the multidimensional nature of current environmental problems. Qualitative analysis is thus relevant at this point since it provides means to analyze ecosystem transformations and the consequences derived from contemporary production practices. Oral testimonies by diverse actors (producers, members of institutions, traders, researchers in the region) were gathered through semi-structured interviews after field visits and later analyzed in the search for agricultural production milestones and their role in the ecological transformation of the region. The findings were contrasted with written sources and documentary records such as agricultural censuses, institutional files, and fieldwork evidence. Results. Four crucial events in the local agricultural development of the Ibagué Fan were reported: the extensive livestock farming around 1900, which lead to the consolidation of four generations of producers; the construction of irrigation channels which benefited large-scale rice production in the area by the midtwentieth century; the combination of rice production, livestock farming and all its associated crops; and finally, the introduction of sustainable livestock farming projects. Implications. Historical analyzes show the need to know the perspective of the actors involved in the development of agriculture and livestock in the region over the years; these milestones are fundamental for the development of public policies that recognize the historical, social and geographical particularities. Conclusions. The history of the colonization of the Colombian territory from the seventeenth century was characterized by the introduction, adaptation, and expansion of the livestock farming culture, together with the populating of the territories near the plains of the Magdalena river, as it was the main connecting route in the region. Keywords: Livestock activity; agriculture practices; local perceptions; agricultural crops.